THE ROLE OF GENERAL ELECTIONS COMMISSION ON TIKTOK TO INCREASE VOTING PARTICIPATION IN THE 2024 ELECTIONS - Rosadi, Raesita Rakhmawati (jfpublisher, 2024)
In 2024, Indonesia conducted its fifth general election, which involved voting for various positions including the President, the Vice President, members of the People’s Consultative Assembly (MPR), the House of Representatives (DPR), and the Regional Representative Council (DPD). Approximately 60 percent of registered voters for this crucial electoral process were young individuals, highlighting their significant potential to influence the country’s political landscape. The role of the General Elections Commission of Indonesia (KPU RI) is crucial in educating young people on the politics, particularly emphasizing their contributions during elections. Political education for the youth has evolved with the emergence of social media platforms, particularly TikTok. This article examines the use of the General Elections Commission’s TikTok account (@KPU_RI) as one of the channels for educating young voters, analyzing its content and its potential impact on fostering politically aware and engaged youth. The research methodology employed in this study is qualitative, focusing on descriptive methods. The research findings identified that the General Elections Commission strategically employs TikTok as a means to educate young voters, utilizing edutainment content revolving around four main themes: democracy, institutions, elections, and political participation. Additionally, the General Elections Commission employ a content marketing strategy to enhance the reach and engagement of their content with young voters.